Elastic-to-plastic crossover below the peak effect in the vortex solid of YBa2Cu3O7 single crystals - Valenzuela, S.O.; Maiorov, B.; Osquiguil, E.; Bekeris, V. (American Physical Society, 2002)
Fil: Maiorov, B. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina